Transformation of new public services in the perspective of responsive law in Indonesia - Khair, Taufiqulhidayat; Mulyanto, Mulyanto (PINISI Discretion Review, 2024)
This research discusses how public services have developed from time to time, until the age of new public services. This research answers what are the differences in public services from time to time, how is the application of new public services in Indonesia by taking a responsive legal perspective, with the issuance of (PERPRES) Number 95 of 2018 concerning Electronic-Based Government Systems which is a derivative of Law Number 25 of 2009 concerning Public Services signifies that new public services have been running in Indonesia and are also developing in regions in Indonesia.